No relevant analogy between COVID-19 and acute mountain sickness - Berger, Marc Moritz; Hackett, Peter; Bärtsch, Peter (High altitude medicine & biology, 2020)
Berger, Marc Moritz, Peter H. Hackett, and Peter Bärtsch. No relevant analogy between COVID-19 and acute mountain sickness. High Alt Med Biol. 21:315-318, 2020.—Clinicians and scientists have suggested therapies for coronavirus disease-19 (COVID-19) that are known to be effective for other medical conditions. A recent publication suggests that pathophysiological mechanisms underlying acute mountain sickness (a syndrome of nonspecific neurological symptoms typically experienced by nonacclimatized individuals at altitudes >2500 m) may overlap with the mechanisms causing COVID-19. In this short review, we briefly evaluate this mistaken analogy and demonstrate that this concept is not supported by scientific evidence.